2019
DOI: 10.1007/978-981-13-6635-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Africa’s Indigenous Knowledge: From Education to Practice

Abstract: This chapter will explore the previous and/or ongoing practice of Africa's indigenous knowledge across selected fields. The chapter will also, where applicable, explore the curriculum of study within the identified fields in order to determine the extent to which the existence and practice of indigenous knowledge is recognized in each.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recent theoretical developments have revealed that, there has been spirited abandoning of traditional African practices and technologies in favor of western civilization alternatives since the conquest of Africa by the European settlers in the 1800 period. African civilizations neglected their tools, equipments and commercial practices in favor of new technologies brought about by the white settlers (Ezeanya-Esiobu, 2019). This seems to be a common problem in Africa and other developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical developments have revealed that, there has been spirited abandoning of traditional African practices and technologies in favor of western civilization alternatives since the conquest of Africa by the European settlers in the 1800 period. African civilizations neglected their tools, equipments and commercial practices in favor of new technologies brought about by the white settlers (Ezeanya-Esiobu, 2019). This seems to be a common problem in Africa and other developing countries.…”
Section: Introductionmentioning
confidence: 99%